Geoenvironmental Engineering: Contaminated Soils, Pollutant Fate, and Mitigation - Yong, Raymond N. (CRC Press, 2009)
Why do some contaminants remain in soils indefinitely? How much of a threat do they pose to human health or the environment? The need for effective and economic site decontamination arises daily. Geoenvironmental Engineering: Contaminated Soils, Pollutant Fate, and Mitigation discusses why soils remain contaminated, focusing on the development of the factors, properties, characteristics, and parameters of soils and individual contaminants.